Pengaruh kualitas website Kandaga terhadap kepuasan pengguna Perpustakaan Pusat Universitas Padjadjaran - Eko Retno Wulandari; Edwin Rizal; Elnovani Lusiana (Jurnal Kajian Informasi dan Perpustakaan, 2021)
Library websites in higher education institutions help increase competitiveness and reinforce institutions, information media, and library promotion. This study aimed to determine the effect of the quality of the Kandaga website partially and simultaneously on user satisfaction at the Padjadjaran University Central Library. This study used an explanatory quantitative approach by distributing questionnaires to 373 people. The analysis of research data used path analysis. Based on the research results, variables of usability quality, service interaction quality, interface quality, and digital library service quality partially had a significant effect on user satisfaction of the Padjadjaran University Central Library. The quality of the Kandaga website had a significant simultaneous effect on user satisfaction of the Central Library of Padjadjaran University by 87.4%. The quality of the digital library services had the most significant influence on user satisfaction, namely 52.6%. The Central Library o Padjadjaan University needed to prioritize digital library service quality improvements because this variable significantly influenced user satisfaction. The quality of the Kandaga website partially and simultaneously had a significant effect on user satisfaction of the Central Library. Information quality had no significant effect on user satisfaction of the Central Library of Padjadjaran University. Kandaga's information quality variable had the highest value. The study concludes that users of the Kandaga website believe that the quality of information on the Kandaga website currently has met user needs, has a good reputation, is trustworthy, relevant, detailed, and easy to understand.